Pengaruh Pengungkapan Corporate Social Responsibility dan Return on Asset terhadap Nilai Perusahaan Manufaktur yang Terdaftar di Jakarta Islamic Index (JII) Tahun 2018-2022 - Oktaviani, Siti Atikah; Tripalupi, Ramadhani Irma; Wardiyah, Mia Lasmi (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The purpose of this research is to find out and analyze the CSR disclosure reporting mechanism; the influence of CSR disclosure on Company Value; the effect of disclosure of ROA on Company Value; and the joint effect of CSR and ROA on Company Value (in Manufacturing Companies registered on JII for 2018-2022. The research method used in this research is Mixed Methods. This research uses the Mixed Methods method with the type of approach in the form of "Embedded Design". This type of approach includes those that free the researcher to choose one of the prioritized methods.The researcher prioritizes quantitative research methods with a larger portion compared to qualitative research methods.The results of the qualitative research show that the CSR disclosure mechanism in Manufacturing sample companies that are listed in JII during 2018-2022 can be said to be good. The results of the research from the quantitative method, namely CSR has a significance value of 0.008 and its partial effect on Company Value is 22.6%. . CSR and ROA have a significance of 0.000, both of which have a simultaneous effect on firm value with an influence of 51.1%.